Advancement in Benthic Microbial Fuel Cells toward Sustainable Bioremediation and Renewable Energy Production - Umar, Mohammad Faisal (Int J Environ Res Public Health, 2021)
Anthropogenic activities are largely responsible for the vast amounts of pollutants such as polycyclic aromatic hydrocarbons, cyanides, phenols, metal derivatives, sulphides, and other chemicals in wastewater. The excess benzene, toluene and xylene (BTX) can cause severe toxicity to living organisms in wastewater. A novel approach to mitigate this problem is the benthic microbial fuel cell (BMFC) setup to produce renewable energy and bio-remediate wastewater aromatic hydrocarbons. Several mechanisms of electrogens have been utilized for the bioremediation of BTX through BMFCs. In the future, BMFCs may be significant for chemical and petrochemical industry wastewater treatment. The distinct factors are considered to evaluate the performance of BMFCs, such as pollutant removal efficiency, power density, and current density, which are discussed by using operating parameters such as, pH, temperature and internal resistance. To further upgrade the BMFC technology, this review summarizes prototype electrode materials, the bioremediation of BTX, and their applications.